Assessing if Challenge Stressors Work as a Source of Motivation Among the Employees in the Indian Banking Industry - Syed, Aamir Aijaz; Gupta, Swati; Rai, Divya; Tripathi, Ravindra (Prabandhan: Indian Journal of Management, 2022)
In today’s scenario, jobs are becoming challenging day by day. Increased competition and technological advancements have made jobs more demanding and stressful, which results in job burnout. This study examined the relationship between job burnout and challenge stressors in the Indian banking industry. To achieve the above objective, qualitative analysis was conducted using 720 validated questionnaires collected via a Google Form. The outcome suggested that challenger stressors significantly impacted job burnout in the Indian banking industry. Overall, 5% variation in job burnout could be forecasted by challenge stressors. The study further concluded that challenge stressors and different facets of burnout (depersonalization and emotional exhaustion) also had a significant and positive impact on job burnout. Lastly, the study highlighted that 6% of personal accomplishment was attributed to positive challenge stressors. The findings will assist in devising appropriate human resources policies for the betterment of employees.